MODERN METHODS IN THE TREATMENT OF CARIES TYPES ACCORDING TO BLACK'S CLASSIFICATION - Muhammadiyeva Kamola Furqat qizi, (TADQIQOTLAR, 2026)
Abstract This article analyzes the types of caries according to Black’s classification, which is considered the classical foundation of dentistry, and the modern technologies used in their treatment. The research highlights minimal invasive preparation methods for Class I-V carious cavities, adhesive systems, and the specific aspects of composite restorations. Furthermore, the article provides a scientific basis for the transformation of traditional Black’s principles according to the requirements of modern dentistry and the effectiveness of aesthetic restoration.